Extinction Status, Challenges, and Conservation Approaches of South African Indigenous and Village Chickens: A Systematic Review - Sindisiwe Mbali Sithole; Khathutshelo Agree Nephawe; Takalani Judas Mpofu; Bohani Mtileni; Masindi Lottus Mphaphathi; Jabulani Nkululeko Ngcobo (Agriculture)
South Africa recognizes the value of indigenous breeds such as Potchefstroom Koekoek, Boschveld, Ovambo, Venda, Naked Neck, and nondescript village chickens. Indigenous chickens support sustainable food systems, improve nutrition, and enhance livelihoods in rural communities, thereby contributing to the United Nations’ Sustainable Development Goal (SDG) 2 on Zero Hunger. These breeds are not only vital to rural farmers for food production, income generation, and subsistence but also provide rural farmers with cheap nutritious protein such as eggs and meat for household consumption. Moreover, they are preferred by rural farmers because they are relatively affordable to produce, can withstand harsh environmental conditions amid accelerated climate change compared to exotic breeds, and require less/no feed supplementation. However, despite the numerous advantages of keeping these chickens, it has been found that they are mostly in danger of extinction due to evolving production methods that favor exotic breeds. Therefore, understanding their extinction status, different implications for conserving their genetic material, challenges encountered, and future approaches to rescue these breeds remain vital. Hence, the aim of this systematic review was to assess the extinction status, challenges, and conservation approaches for these breeds. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were utilized to search for suitable articles addressing the objective of the current review. Research articles were grouped and evaluated for eligibility, and the data from the Domestic Animal Diversity Information System database were used. Records such as duplicates of studies addressing origins, phenotypic and genetic diversity, the conservation of indigenous chickens, semen cryopreservation of indigenous chickens, climate change effects on indigenous chickens, and the use of extenders with exotic chickens and other chicken types, reports in other languages, and reports that were inaccessible were excluded. Articles addressing origins, phenotypic and genetic diversity, the conservation of indigenous chickens, semen cryopreservation of indigenous chickens, climate change effects on indigenous chickens, and the use of extenders with indigenous chickens were included in this review. The keywords used to search articles online were as follows: South African indigenous chicken; extension status; conservation; genetic resources; genetic markers; effective population size; inbreeding; and characterization. This systematic review found that there is less information in the Domestic Animal Diversity Information System regarding South African indigenous and village chickens, suggesting a lack of reporting in this system. Moreover, our review confirmed that most South African indigenous chickens are threatened and, hence, require interventions such as assisted reproductive technologies and other strategies in order to improve efficiency.